Information communication and community strategies for facing drought in Cuba. Experiences - Pedroso Aguiar, Willy (2017)
Cuba has been hit since three years ago by a severe drought that has affected most of the country's municipalities. Response strategies should implement information and communication processes that favor efficiency, articulation, knowledge management and citizen participation. In an approach to community strategies to overcome this situation, the communication and information practices that underlie drought management in selected localities are described. The study was conducted from an interdisciplinary approach between the information and communication sciences. Among the findings, there are strong differences between the infocommunicational activity of community self-organization and the activities of water management actors.